Design and Implementation of Three Phase PWM Inverter Control Using Microcontroller - Kalyankolo, Umaru; Kigenyi, Abdunulu; Kavuma, Lawrence; Isabirye, William; Edozie, Enerst; Kalyankolo, Zaina (International Journal of Engineering and Information Systems, 2021)
This paper presents an advanced three phase inverter topology the Z-Source Inverter and its control using microcontroller Atmega 328P. Z-Source Inverter employs second order filter network at front end which provides unique buckboost feature for inverter. Z-Source inverter can be controlled by any traditional PWM method. Here the modified maximum constant boost PWM method is utilized for Z-Source inverter control. The microcontroller Atmega 328P is used to generate PWM pulses and to control operation of Z-Source inverter. The complete hardware is designed to drive the three phase induction motor. The hardware design involves the design of control circuit, driver circuit, Z-Source network, main inverter bridge, power supply etc. The Z-Source inverter is implemented and tested to verify the Z-Source inverter concept. The desired three phase PWM signals are generated by using control circuit and detailed hardware results are presented.
Keywords: driver, maximum constant boost, microcontroller, PWM, voltage boost, Z-Source Inverter